2015
DOI: 10.1093/cercor/bhu325
|View full text |Cite
|
Sign up to set email alerts
|

Neural Systems Involved When Attending to a Speaker

Abstract: Remembering what a speaker said depends on attention. During conversational speech, the emphasis is on working memory, but listening to a lecture encourages episodic memory encoding. With simultaneous interference from background speech, the need for auditory vigilance increases. We recreated these context-dependent demands on auditory attention in 2 ways. The first was to require participants to attend to one speaker in either the absence or presence of a distracting background speaker. The second was to alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…These components are extracted in a data driven manner, with the timecourse of each component regressed against the experimental design to establish the component's task relatedness (Calhoun, Adali, Pearlson, & Pekar, 2001; see examples from Braga, Wilson, Sharp, Wise, & Leech, 2013;Kamourieh et al, 2015). Whilst ICA is unable to assess causal relations in the functional connectivity between regions, it does have the advantage that it can be conducted on the whole brain without prior assumptions about the underlying structure of functional networks.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These components are extracted in a data driven manner, with the timecourse of each component regressed against the experimental design to establish the component's task relatedness (Calhoun, Adali, Pearlson, & Pekar, 2001; see examples from Braga, Wilson, Sharp, Wise, & Leech, 2013;Kamourieh et al, 2015). Whilst ICA is unable to assess causal relations in the functional connectivity between regions, it does have the advantage that it can be conducted on the whole brain without prior assumptions about the underlying structure of functional networks.…”
Section: Future Directionsmentioning
confidence: 99%
“…This may be a useful approach for studying effortful listening, which has previously been shown to engage both domain-general attentional and domain-specific sensory systems (Binder et al, 2004;Evans et al, 2016;Vaden et al, 2013;Wild et al, 2012). Furthermore, the ability to de-mix neural signals into functionally independent networks may be of particular benefit in complex experimental designs in which multiple events occur simultaneously within a trial, for example in "cocktail party listening" or speaking in noise (Braga et al, 2013;Evans et al, 2016;Kamourieh et al, 2015;Meekings et al, 2016). Finally, an additional advantage of ICA is that components from a particular study can be compared to those extracted from large scale studies of resting state networks by correlating the spatial maps (Smith et al, 2009).…”
Section: Future Directionsmentioning
confidence: 99%
“…This possibility seems plausible as well. Several neuroimaging studies have observed FEF activity with tasks of auditory spatial attention (Kamourieh et al, 2015;Mayer, Harrington, Adair, & Lee, 2006;Salmi, Rinne, Koistinen, Salonen, & Alho, 2009;Wu, Weissman, Roberts, & Woldorff, 2007). Using magnetoencephalography (MEG) and stimulation with two simultaneous virtual sound sources, Lee et al (2013) found enhanced activity in left FEF prior to and throughout the auditory stimulus when subjects directed auditory attention to target location compared to when they focused on target pitch.…”
Section: N2acmentioning
confidence: 99%
“…Both these streams might converge in frontal cortex (ZĂŒndorf, Lewald, & Karnath, ). With cocktail‐party tasks, specific networks have been revealed, namely, posterior superior temporal gyrus (STG), including planum temporale, IPL, inferior frontal and dorsofrontal cortices, as well as pre‐ and postcentral areas (e.g., Bharadwaj, Lee, & Shinn‐Cunningham, ; Kamourieh et al, ; Lee et al, ; Lewald & Getzmann, ; ZĂŒndorf, Karnath, & Lewald, ; ZĂŒndorf, Lewald, & Karnath, ).…”
mentioning
confidence: 99%
“…Such an analysis is fundamental to the initial parsing of a musical 'scene', before more detailed analysis can occur [7]; it is likely to entail an interaction of bottom-up mechanisms for coding perceptual structure with top-down mechanisms for resolving perceptual ambiguities based on stored templates or schemas derived from past experience of music [5,67]. Musical scene analysis has not been widely studied neuropsychologically in clinical populations but is likely to engage posterior superior temporal and parietal lobe regions and their dorsal projections [68][69][70][71][72]. AD has been shown to produce a generic impairment of auditory scene analysis under diverse listening tasks and conditions, including the streaming of sound sequences that bear some similarities to musical melodies; this has been linked to dysfunction of posterior temporoparietal areas overlapping those involved in music perception [33,35,36,[73][74][75].…”
Section: Introductionmentioning
confidence: 99%